POST DELINEATION ANALYSIS OF BAYAN STRUCTURE TARAKAN BASIN EAST KALIMANTAN - RUSLI, SAIFATUR
Hydrocarbon exploration in the Tarakan Basin East Kalimantan was done to find economics oil and gas reserves. The complexity of sand body reservoir in deltaic system can cause ambiguity of interpretation and analysis. Essentially, best optimism resulted by combining geophysics, geology, petrophysics and reservoir characterization studies. However, integrating information from different studies is not easy even though supported by the availability of GGR (Geology, Geophysics and Reservoir) data and modern software. This approach is describing and illustrating by some examples in this research. Delineation of Bayan Structure in the Tarakan Basin at Middle – Late Miocene Meliat Formation shows two principal facts, well A1 is proven discovery to be filled by gas based on reservoir testing and Wells A-2B and A3 are dry. These facts lead to interpretation and analysis of GGR information to be scientific answer for the unsuccessful delineation Well A-2B and A3. Detailed reservoir analysis was applied to trace the lateral continuity sandstone reservoir of Meliat Formation. Four zones of sandstone reservoir of Meliat Formation have average thickness of 7 – 19 ft. RMS amplitude maps from 3D seismic data was used to identify the lateral continuity sandstone reservoir of Meliat Formation. The RMS amplitude maps show the positions of delineation Well A-2B and A3 exist on different sand body reservoir to well A1. Practically, there are stratigraphic compartments. The results of stratigrapic sequence correlations in reservoir scale show sandstone Reservoir 1, 2 and 3 of Well A1 experiencing shale-out to Well A3 whereas Reservoir 4 is developing in Well A3. Reservoir 3 and 4 in Well A-2B are iv developing with intermediate porosity category while Reservoir 1 and 2 experiencing shale-out in this well. Trap modeling hydrocarbon analysis shows Reservoir 4 actually developed in Well A3. Even though the reservoir is over LIG but this reservoir body is exist differently from Reservoir 4 of Well A1. In Well A-2B the Reservoir 1 and 2 are undergone shale-out whereas Reservoir 3 and 4 exist on the different sand body with Reservoir 3 and 4 of Well A1 that can explain why Wells A-2B and A3 contained by water. Porosity and density analysis are also indicated that these sand bodies were involved with diagenetic process which characterizing by porosity decrease and density increase from Well A1 to Wells A-2B and A3.